Factors influencing the quality of life in patients with severe dementia. Issue 1 (13th October 2021) - Nagata, Yuma; Nishikawa, Takashi; Tanaka, Hiroyuki; Ishimaru, Daiki; Ogawa, Yasuhiro; Fukuhara, Keita; Shigenobu, Kazue; Ikeda, Manabu
Abstract: Background: A comprehensive understanding of the relevant factors involved in improving quality of life (QoL) is essential in patients with severe dementia; however, rating scales used in previous studies may not adequately reflect the factors that affect these patients. The purpose of this study was to identify factors that contribute to QoL using an evaluation scale suitable for patients with severe dementia. Methods: The current cross‐sectional study was conducted at a hospital for recuperation in Hyogo prefecture in Japan. The measurement scales included the QoL in Late‐Stage Dementia Japanese version (QUALID‐J), Cognitive Test for Severe Dementia, Neuropsychiatric Inventory‐Nursing Home (NPI‐NH), Physical Self‐Maintenance Scale (PSMS), Pain Assessment in Advanced Dementia (PAINAD), and Special Care Unit Environment Quality Scale (SCUEQS). Multiple regression analyses were performed. Results: We assessed a total of 105 patients with severe dementia (80 women; aged 87.3 ± 6.3 years). Multiple regression demonstrated that the QUALID‐J total score was significantly affected by the NPI‐NH and PAINAD scores. Factors 1 (expression of comfort) and 2 (expression of discomfort) of the QUALID‐J were significantly affected by the PSMS and PAINAD, and the NPI‐NH and PAINAD scores, respectively. Conclusion: Our results indicate that behavioural and psychological symptoms of dementia and pain are important factors in influencing the QoL of patients with severe dementia.